Problematika Penerapan Pembelajaran Problem Based Learning pada Mata Pelajaran Akidah Akhlak - Rokim, Rokim (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2024)
The 2013 curriculum regulations require learning to use a student-centered or scientific approach, but in reality the majority of teachers still use conservative learning for reasons of making learning easier for teachers, adapting to students' characteristics, adjusting the dimensions of knowledge and learning objectives, even though in a number of studies it has received a lot of criticism from experts because this kind of learning makes students passive and not creative in building knowledge. From this phenomenon, I present a problem based learning model as part of the learning approach for students at madrasah ibtidaiyah level in Islamic religious education subjects. The aim is to find out what problems teachers have in operationalizing the problem based leaning model and what the learning problems are like for students in elementary age children in the Aqidah Akhlak subject whose dimensions of knowledge are mostly conceptual and religious doctrine.This research uses a qualitative approach and field research which is useful for describing learning activities in the classroom.The findings from the research are the most crucial problem in the first syntax when the teacher presents teaching material in the form of text for students to understand, plus fatal apperception, the formation of groups that are not heterogeneous, student participation is weak, learning references are limited, and, unfocused learning objectives.